For a social evaluation of new communication and information technologies - Tello-Charún, Max R. (1988)
We know that the demands of post-industrial societies were the pressure for technological change to take place; but we do not know what will be the consequences of incorporating these innovations into pre-industrial or developing societies. In any case, it is necessary to propose research instruments that allow diagnosing and evaluating the sociocultural and psychosocial effects of the possible incorporations in order to sustain policies and strategies according to our needs.